Politically Incorrect Statements Do Not Make Leaders Seem More Trustworthy: Randomized Experiments Exploring the Perceptual Consequences of Political Incorrectness. (August 2019) - Arnestad, Mads Nordmo
Several political analysts, communication strategists, and academics have speculated that leaders who openly defy the norms of political correctness may gain a reputation for honesty and integrity, which may make them come across as more trustworthy. The present article reports the results from two randomized vignette-based experiments exploring the potential link between managers' political incorrectness and perceived trustworthiness. The results offer no support for the notion that managers who make politically incorrect statements will come across as more trustworthy. On the contrary, the levels of perceived trustworthiness were found to be substantially lower for managers who express politically incorrect views, compared with those who express contrasting politically correct views.